Sarcomas in pregnancy: Report of two cases and literature review - Ibargüengoitia-Ochoa, Francisco (2020)
Objective: To present the perinatal results of two patients diagnosed with Ewing's sarcoma and alveolar rhabdomyosarcoma. Methodology: Two cases of patients with a diagnosis of sarcoma treated at the National Institute of Perinatology in Mexico City were reviewed. Results: Case 1, a 22-year-old female, with a 23.0-week pregnancy and a 20-cm tumor in the left gluteal region, pain and difficulty walking. The chest radiograph revealed multiple pulmonary nodules and the magnetic resonance imaging revealed a tumor in the gluteal region with extensive involvement. The diagnosis was stage IV metastatic Ewing sarcoma. Management consisted of symptomatic treatment with resolution of the pregnancy at 28 weeks. Case 2, a 22-year-old female with a 12.0-week pregnancy and a diagnosis of metastatic spinal cord syndrome. T9-11 decompression was performed. Absence of fetal heart rate was evidenced, so medical management of deferred abortion was performed.